Algerian university libraries and the digital age: new communication behaviors. Issue 1 (12th January 2015) - Bernaoui, Radia; HASSOUN, MOHAMED
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to clarify the digital era and to explain that these changes have given rise to the existence of several communities or consortia in higher education of Algeria in order to bring users closer. Various changes linked to advancement in information technologies have changed work methods and behavior among professionals in the information and communication sciences field. Design/methodology/approach – The paper opted for a survey which was organized into two principal phases. An exploratory phase that consisted of undertaking qualitative interviews and another phase followed by a preliminary survey (pilot study) to prepare for the definitive survey. In this way that the authors chose a sample of a total of 50 questionnaires. The authors succeeded in obtaining a total of 30 respondents, representing a response rate of 60 percent. Findings – The preliminary survey reveals that the Algerian university libraries wish to create a community of exchange and collaborative work between professional colleagues in this new digital age. Research limitations/implications – This study is a beginning of a research on the behaviors of professionals in Algerian university libraries. A national survey is about to be performed in order to analyze more better the new communication behaviors. Practical implications – The paper includes implications for changing the new behavior of professionals in university libraries in order to be adapted in this new digital age that requires us to work in the library without walls. Originality/value – The originality of this paper is to discuss the subject of the digital libraries, the information retrieval and the collaborative work environments and the Semantic Web.